IDENTITY CONSTRUCTION OF INDONESIAN NON-MILITARY ESP TEACHERS’ PERSONAL EXPERIENCES: A NARRATIVE INQUIRY - Evi Martiningsih (Graduate Program, University of Islam Malang, 2021)
The global influence that has an impact on the professional life of teachers has brought about a change in the growing popularity of teaching English for specific purposes. The empirical reality is that there is a long process to become an ESP teacher. However, some difficulties may arise as teachers adapt to ESP teaching. This study examines how military English teachers negotiate, construct, and develop identity construction at a military college in Indonesia to discover the challenges that ESP teachers face as they construct their identities.This narrative study explores life experience interview data to examine the identity construction of two non-military ESP teachers at a military college in Surabaya, Indonesia. Based on a model adapted from the identity of a TESOL teacher (Pennington, 2014), Tao and Gao (2018). Analysis of the data revealed that for study participants who became ESP teachers, to be precise, Military English was a complex process for changing professional practice and building a professional identity. It describes how teachers engage with their professional lives to meet the demands of ESP learning and face challenges in building their professionalism.The findings illustrate the identity construction that institutional and professional contexts play a role in building the identity of ESP teachers. This suggests that institutions play an important role in constructing professional identities as teachers progress through their careers. Although each identity framework contains characteristics that describe how teachers construct their identities, the five frameworks interact to shape the perception and position of teachers in military colleges.Keywords: teacher identity, ESP teachers, a non-military, military college,